2023
DOI: 10.18666/jorel-2023-11642
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining Civic Recreation: Understanding What Shapes Climbers’ Contributions to Local Resource Stewardship and Advocacy

Abstract: A new form of recreation-focused collective action has grown over recent decades. Practitioners of shared outdoor recreation interests are coordinating to meet stewardship and advocacy goals. Such "civic recreation organizations" blur the lines between voluntary sport clubs, interest groups, and resource management, promising concentrated recreational benefits and offering the potential for positive impacts for other user groups and stakeholders, land managers, and perhaps even the general public. This study d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Regardless, it is obvious that awareness of CBC is required to report bats to the organization. Similarly, Carter (2023) found that familiarity with a civic recreation organization was positively related to rock climbers engaging in volunteer behavior. A local liaison as suggested by the world café data may be able to not only increase the awareness of CBC but also correct any misinformation regarding the organization.…”
Section: Answersmentioning
confidence: 90%
“…Regardless, it is obvious that awareness of CBC is required to report bats to the organization. Similarly, Carter (2023) found that familiarity with a civic recreation organization was positively related to rock climbers engaging in volunteer behavior. A local liaison as suggested by the world café data may be able to not only increase the awareness of CBC but also correct any misinformation regarding the organization.…”
Section: Answersmentioning
confidence: 90%